Isolation and identification of yeast species involved in cocoa shallow box fermentation - Ooi, Teng Sin (Universiti Malaysia Sarawak (UNIMAS), 2012)
Research was performed to correlate sugar content, pH of pulps and nibs and temperature with the yeast species involved in cocoa fermentation process in Perak and Samarahan at different fermentation periods. The pH of pulps and nibs had an inversely proportional relationship where a decrement in the pH of pulps would cause an increment in the pH of nibs. The temperature at both areas had shown the same pattern where the highest temperature was stated at the 72 hours fermentation period and fluctuated after that as a result of turning of cocoa bean process. The sugar content of the Perak samples was initially high but decreased to 5.1 Brix at the end of fermentation due to microorganism reaction. The sugar content of the Samarahan samples was initially low but increased to 6.5 Brix at the end of cocoa fermentation process due to pectinolytic activity. 21 yeast isolates were isolated from both places. Four yeast isolates were managed to be sequenced and two species were identified as Candida krusei and Pichia anomala. Further identification using PCR molecular technique need to be carried out to identify and find out more about different types of yeast species involved at different cocoa fermentation periods.